Teaching effectiveness of instructors during lectures in pre-clinical phase, School of Medical Sciences, USM - Ismail, Muhd Al-Aarifin (2016)
INTRODUCTION Teaching is one of the major roles as a medical teacher. Effective teaching means better students’ learning and ultimately will improve educational outcomes. Teaching evaluation is a vital activity in any curriculum. With proper feedback system, it will lead to improvement of teaching skill among faculty members. OBJECTIVES The purpose of this study was to evaluate lecturers’ teaching effectiveness during lectures in pre-clinical years USM medical school through medical students’ ratings by determining level of teaching behaviors. It was also to determine factors (gender, ethnic groups, specialties and designation) that associate with the lecturers’ teaching effectiveness. METHODOLOGY This study utilized a cross-sectional design. Faculty members in School of Medical Sciences, USM who has been involved in delivering lecture for pre-clinical year students were chosen as study subjects. 30 pre-clinical year students were trained to rate their teaching behavior by using validated instrument. School and ethical committee clearance were obtained prior to the start of the study. Data collection wasdone in 4 months’ time and it was analyzed using Statistical Package for Social Sciences (SPSS) version 22. RESULTS A total of 55 instructors were involved. They attained good level of teaching behavior in the aspects of organisation and speech & pacing as indicated by the mean scores of 4.02 and 4.15 respectively. For the clarity, enthusiasm, interaction and rapport aspects, they attained acceptable level of teaching behaviors as suggested by mean scores ranging from 3.10 – 3.59. Meanwhile the lowest level was in disclosure aspect with mean score of 2.20. There were no significant relationship seen between teaching behaviors and all observed factors (i.e. instructors’ gender, ethnic group, specialty and designation), CONCLUSION USM medical school pre-clinical instructors were positively perceived in the aspects of organisation and speech & pacing. The clarity, enthusiasm, interaction and rapport aspects were under areas for improvement and the disclosure aspect was an area of concern. Teaching behaviors were not associated with gender, ethnic group, area of expertise and designation. However, non-clinical instructors were better perceived than the clinical instructors in several low-inference teaching behaviors.